2006
DOI: 10.1183/09031936.06.00054105
|View full text |Cite
|
Sign up to set email alerts
|

Occult alveolar haemorrhage in pulmonary veno-occlusive disease

Abstract: Pulmonary veno-occlusive disease (PVOD) is a rare cause of pulmonary arterial hypertension that affects predominantly post-capillary pulmonary vessels. A major concern with PVOD is the poor response to available therapies and the risk of pulmonary oedema with continuous intravenous epoprostenol.The present authors hypothesised that alveolar haemorrhage may be a characteristic feature of pulmonary veno-occlusive disease, as compared with other forms of pulmonary arterial hypertension that predominantly involve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
111
0
13

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 131 publications
(127 citation statements)
references
References 38 publications
3
111
0
13
Order By: Relevance
“…Pleural effusions have been suggested to be more frequent in PVOD, however, the studies focused on radiography with high-resolution computed tomography (HRCT) of the chest show a similar proportion of pleural effusions in both diseases [8,10,48,49]. Hemoptysis has been described in PVOD; however, in our recent study, hemoptysis was reported infrequently and equally in both idiopathic PAH and PVOD, confirming that alveolar hemorrhage in PVOD is generally occult [8,50]. Clubbing and Raynauld's phenomenon have been reported as clinical signs in PVOD but this was not reproduced in our recent series, as these signs remain rare and can also occur in idiopathic PAH [8].…”
Section: Clinical Presentationmentioning
confidence: 74%
See 4 more Smart Citations
“…Pleural effusions have been suggested to be more frequent in PVOD, however, the studies focused on radiography with high-resolution computed tomography (HRCT) of the chest show a similar proportion of pleural effusions in both diseases [8,10,48,49]. Hemoptysis has been described in PVOD; however, in our recent study, hemoptysis was reported infrequently and equally in both idiopathic PAH and PVOD, confirming that alveolar hemorrhage in PVOD is generally occult [8,50]. Clubbing and Raynauld's phenomenon have been reported as clinical signs in PVOD but this was not reproduced in our recent series, as these signs remain rare and can also occur in idiopathic PAH [8].…”
Section: Clinical Presentationmentioning
confidence: 74%
“…Moreover, post-capillary obstruction may frequently lead to capillary angiectasia and even capillary angioproliferation; in PVOD cases, doubling and trebling of the alveolar septal capillary layers may be focally present. Lately, this histological peculiarity has raised questions concerning a possible overlap between PVOD and cases of PCH, a disease classically characterized by an aggressive patch-like Occult pulmonary hemorrhage regularly occurs in patients displaying PVOD contrarily to idiopathic PAH where alveolar hemorrhage is classically absent [50]. This is possibly due to the post-capillary bloc, and is of particular diagnostic interest, as broncho alveolar lavage (BAL) can reveal the presence of occult hemorrhage.…”
Section: Histopathological Assessmentmentioning
confidence: 99%
See 3 more Smart Citations